Implementation of REACH in the new member states. Part one: overview of the chemical and specialty chemical sector in the new member states. Part two: business case studies in selected new member states (Seville, 2006)
"The DG JRC/IPTS has contributed to the analysis of the potential impacts of REACH in the New Member States with two studies: I) Overview of the chemical and specialty chemical sector in the New Member States, which is presented in Part one of this report; II) Business case studies in selected New Member states, of which the findings are presented in this document, part two of the report."